Evaluating the potential impact of bird predation on the SW Atlantic fiddler crab Leptuca uruguayensis - Ribeiro, Pablo Damián; Navarro, Diego; Jaureguy, Luciano M.; Daleo, Pedro; Iribarne, Oscar Osvaldo (Helgoland Marine Research)
The southernmost permanent population of the fiddler crab Leptuca uruguayensis occurs along the Samborombón Bay (36°22′S, 56°45′W, Argentina), an important feeding site for many bird species, including ruddy turnstones (Arenaria interpres), whimbrels (Numenius phaeopus), grey plovers (Pluvialis squatarola), american golden plovers (Pluvialis dominica) and gull-billed terns (Gelochelidon nilotica). Although all these birds are known to prey on many fiddler crab species worldwide, there is no estimation of their joint predation impacts, probably due to the difficulty in conducting experiments on an appropriate spatial scale. In these situations, computer simulation methods are useful tools. By using Monte Carlo methods and field data, we modeled the decrease of a fiddler crab population due to bird predation. The model found that under current bird occurrences and crab densities, birds do not consume more than 0.03% of the studied fiddler crab populations. Birds only consume more than 10% of the population if crab density is below 0.02 crabs m2, or if bird occurrences are at least 3 orders of magnitude higher than currently observed. Both situations are unlikely, as mean crab density is 140 crabs m2, and bird density is never so high. Furthermore, by monitoring three different fiddler crab patches, we found that bird predation cannot account for temporal density changes, suggesting that other population processes are more important than bird predation. In conclusion, even though fiddler crabs may exhibit strong predator-Avoidance behavior, direct lethal effects of bird predation are currently small. Fil: Ribeiro, Pablo Damián. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Navarro, Diego. Consejo Nacional de Investigaciones Científicas y Técnicas. ...